Integration of microbubbles with biomaterials in tissue engineering for pharmaceutical purposes. Issue 6 (June 2020) - Esmaeili, Javad; Rezaei, Farnoush Sadat; Beram, Farzaneh Mahmoudi; Barati, Abolfazl
Abstract: Tissue engineering with the aid of biomaterials is a novel and promising knowledge aiming at improving human life expectancy. Besides, microbubbles are increasingly employed in biomedical applications due to their capability as a reservoir of therapeutic agents and oxygen molecules. In the present study, Microbubbles as the backbone of the research are produced as one of the potent devices in tissue engineering approaches, including drug delivery, wound healing, 3D printing, and scaffolding. It was shown that microbubbles are capable of promoting oxygen penetration and boosting the wound healing process by supplying adequate oxygen. Microbubbles also demonstrated their strength and potency in advancing drug delivery systems by reinforcing mass transfer phenomena. Furthermore, microbubbles developed the mechanical and biological characteristics of engineered scaffolds by manipulating the pores. Increasing cell survival, the biological activity of cells, angiogenesis, cell migration, and also nutrient diffusion into the inner layers of the scaffold were other achievements by microbubbles. In conclusion, the interest of biomedical communities in simultaneous usage of microbubbles and biomaterials under tissue engineering approaches experiences remarkable growth in Pharmaceutical studies. Abstract : Biomedical engineering; Bioengineering; Chemical engineering; Biochemical engineering; Drug delivery; Nanoparticles; Microbubble; Biomaterial; Tissue engineering; Scaffold, Oxygen